2008
DOI: 10.1523/jneurosci.0514-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Facilitates both Phosphatidylinositol 3-Kinase/Akt and ERK1/2 Mitogen-Activated Protein Kinase Membrane Signaling Required for Long-Term Neuropeptide Y Transcriptional Regulation in Clonal, Immortalized Neurons

Abstract: It is established that increases in neuropeptide Y (NPY) expression are associated with hyperphagia and obesity. These effects can be reversed by estrogen, a recognized anorexigen. We found that 17␤-estradiol (E 2 ) regulates biphasic NPY gene expression in a clonal, immortalized hypothalamic cell line, N-38, through estrogen receptor (ER) action at the level of the NPY promoter. However, rapid, nongenomic actions of estrogen, linked to the phosphatidylinositol 3-kinase (PI3-K)/Akt and ERK1/2 mitogen-activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 59 publications
4
40
1
Order By: Relevance
“…The experiments completed in this study were inspired by earlier work from our lab that showed that E 2 decreased NPY mRNA expression in the mHypoE-38 and mHypoE-42 neurons based through PI3K-and MAPK-dependent mechanisms. 19,23 Our findings extend these studies by providing the first evidence that acute E 2 exposure can directly regulate NPY secretion. Here, using clonal, immortalized, hypothalamic, NPY-expressing cell lines we investigated the direct regulation of the orexigenic neuropeptide NPY as a central target for E 2 .…”
Section: Discussionsupporting
confidence: 79%
“…The experiments completed in this study were inspired by earlier work from our lab that showed that E 2 decreased NPY mRNA expression in the mHypoE-38 and mHypoE-42 neurons based through PI3K-and MAPK-dependent mechanisms. 19,23 Our findings extend these studies by providing the first evidence that acute E 2 exposure can directly regulate NPY secretion. Here, using clonal, immortalized, hypothalamic, NPY-expressing cell lines we investigated the direct regulation of the orexigenic neuropeptide NPY as a central target for E 2 .…”
Section: Discussionsupporting
confidence: 79%
“…Intracellular regulatory cascades such as extracellular signal-regulated kinase/ mitogen-activated protein kinases (ERK/MAPK) and PI3-K have been shown to be stimulated by estrogen in diverse cell types, such as tumor cells and neurons [30,39,40,43]. A non-transcriptional mechanism for ER signaling in human as well as in animal endothelial cells was also described, showing that ER can physically and functionally couple to PI3K.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, E 2 can activate PI3K through protein-protein interactions between ERα and p85 (a regulatory subunit of PI3K), which in turn activate Akt in a variety of cell types, including hypothalamic neurons, a process that is completely inhibited by the PI3K inhibitors wortmannin and LY294004 (43,44). We therefore tested whether E 2 activates Akt via ERE-independent ERα signaling in Erα +/+ , Erα -/-, and Erα -/AA mice by immunocytochemistry for pAkt in the ARC and vlVMN of the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%